Severity of Degeneration and Incidence of Knee Pain Induced by Valgus or Varus Stress in Patients with Medical Compartemental Osteoarthritis of the Knee - YOSHIDA, Takuji (Japanese Journal of Rheumatism and Joint Surgery, 2000)
The purposes of this study were to clarify the incidence of pain caused by valgus and varus stress applied to osteoarthritic knees and to describe the clinical implications for pathogenesis of the disease. The subjects of this study were 327 medial compartmental osteoarthritic knees of 238 patients (192 women, 46 men), which had indications for surgical treatment. The age of the patients ranged from 47 to 83 years, with an average of 65.3. The valgus stress maneuver was manually carried out in knees flexed at 30 degrees, and varus stress maneuver was performed in knees extended at 0 degress. The antero-posterior radiograms of the knee joint were taken in the standing leg and under both valgus- and varus-stressed conditions with application of 15 kilopascals using Telos fixative equipment. The femoro-tibial angle (FTA) was measured in these three radiograms, and a swaying angle was obtained by subtracting valgus-stressed FTA from varus-stressed FTA. Knee pain was most frequently induced by valgus stress, which was found in 226 knees (69.1%) . Concerning the site of pain, it was present in the medial side in 197 knees, the lateral in 24 knees, and the entire area of the knee joint in 5 knees. On the other hand, knee pain induced by varus stress was seen in 90 knees (27.5%) . Pain was on the medial side in 88 knees, on the lateral in one, and over the entire area in one. The sign of medial kneepain elicited by the valgus-stress maneuver was the most reliable and reproducible among the other pain inducing stress tests in cases of medial compartmental osteoarthritis of the knee. Standing-FTA ranged from 175° to 208°, with a mean of 185.5°. The swaying angle ranged from 1° to 30°, with a mean of 10.8°. Swaying angle and standing-FTA were greater in the knees with medial knee pain elicited by valgus stress than in those without pain (p<0.05) . The results suggest that the incidence of pain provoked by valgus stress is strongly correlated with severity of degeneration in knees affected by medial compartmental osteoarthritis, and this maneuver may serve as an indication in determining the necessity and type of surgical treatment.